RONC-01. PROTON BEAM THERAPY IN THE MULTIDISCIPLINARY THERAPY FOR PEDIATRIC BRAIN AND SPINAL TUMOR AT KOBE CHILDREN'S HOSPITAL WITH KOBE PROTON CENTER. (4th December 2020) - Kawamura, Atsufumi; Koyama, Junji; Akutsu, Nobuyuki; Demizu, Yuske; Fukumitsu, Nobuyoshi; Soejima, Toshinori; Kosaka, Yoshiyuki
Abstract: It could be remarked that Radiotherapy (RT) has the important role for the multidisciplinary therapy to Malignant Pediatric Central Nervous System tumor. And recently among RT, Proton Beam Therapy (PBT) is expected to be effective and decrease serious late effects after RT in malignant pediatric tumor. PBT could be controlled precisely the dose and depth and spare the normal structures outside the target. Thus, PBT becomes applicable for pediatric solid tumor to insurance in April, 2016 in Japan. We have worked in closer cooperation with Hyogo Prefectural Ion Beam Medical Center and started PBT from April 2015. And from December 2017, our PBT has transferred to adjacent new medical center (Kobe Proton Center) which has the only institute that equipped the exclusive gantry for children in our country. The treated cases are 28 boys and 35 girls (age average 8.2 years oid). They are 15 Germ cell tumor, 14 Ependymoma, 13 Medulloblastoma, 4 Chordoma, 4 Atypical teratoid/rhabdoid tumor, 2 Craniopharyngioma and others. We have simulated the applications of not only broad beam but also scanned beam to limit the dose distribution and prepare for the cranio-spinal irradiation. All cases underwent magnetic resonance imaging to evaluate the results at out clinic and also the complications are assessed after treatments. The effect of PBT in this series is similar to our experience of traditional RT. There are a few controllable complications such as conventional RT. Farther more follow up is necessary to evaluate the advantage of PBT which could reduce delayed complications of RT.